Dark paradise : Pacific Islands in the nineteenth-century British imagination - Fuller, Jenn (Edinburgh : Edinburgh University Press, 2016)
Examines the way in which the British transformed the Pacific islands during the nineteenth century. The discovery of the Pacific islands amplified the qualities of mystery and exoticism already associated with 'foreign' islands. Their 'savage' peoples, their isolation, and their sheer beauty fascinated British visitors across the long nineteenth century. Dark Paradise argues that while the British originally believed the islands to be commercial paradises or perfect sites for missionary endeavours, as the century progressed, their optimistic vision transformed to portray darker realities. As a result, these islands act as a 'breaking point' for British theories of imperialism, colonialism, and identity. The book traces the changing British attitudes towards imperial settlement as the early view of 'island as paradise' gives way to a fear of the hostile islanders and examines how this revelation undermined a key tenant of British imperialism - that they were the 'superior' or 'civilized' islanders. Key Features. The first monograph to trace the Pacific islands as represented through the lens of British fiction and non-fiction across the long nineteenth century Examines texts written by Pacific islanders and published in the British press Significantly broadens our understanding of the British Pacific by analysing understudied Pacific texts and authors alongside more canonical works
Moving missions and novel settlements : early British Pacific propaganda (1796-1866) -- Adventures in the Pacific : the influence of trade on the South Seas novel -- Islands of discovery : scientific curiosity in the works of Darwin, Huxley and Wells -- The price of paradise : Robert Louis Stevenson, Joseph Conrad and British expansion in the Pacific -- The islanders speak : Pacific reflections in the British press.
Includes bibliographical references (pages 180-190) and index.
Print version record.
JSTOR
Keywords: English literature -- 19th century -- History and criticism; Literature and society -- Great Britain -- History -- 19th century; Islands of the Pacific -- In literature; Oceania -- In literature; Littérature anglaise -- 19e siècle -- Histoire et critique; Littérature et société -- Grande-Bretagne -- Histoire -- 19e siècle.; Pacifique, Îles du -- Dans la littérature.; Océanie -- Dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; English literature; Literature; Literature and society; Great Britain; Oceania; Pacific Ocean -- Islands of the Pacific; 1800-1899; Electronic books; Criticism, interpretation, etc; History